(untitled) (Heritage, 2020)
The subject of this paper is the influence of cultural heritage on the attractiveness of a tourist destination. Countries, as bearers of the brand, have become aware that it is no longer enough to invest only in the development of individual tourist destinations, such as those related to maritime tourism, metropolises, ski resorts or spas. To modern tourists, the whole country must be presented as a tourist destination, and cultural-historical tourism is imposed as the best option. This was influenced by the fact that with the development of society, there have been major changes in the habits, desires, but also the needs of tourists, who today want different types of vacation. The aim of this paper is to present the marketing potentials of the cultural and historical heritage of Serbia.